Venous Aneurysm Complicating Dialytic Arteriovenous Fistula - Nambiar, Arjun K. (Springer-Verlag, 2012)
A case of venous aneurysm complicating arteriovenous fistula created for chronic haemodialysis is presented. The patient underwent successful ligation and excision of the fistula and creation of a fistula on the opposite limb.